An analysis of causal relationship between economic growth and financial development for Turkey: A MODWT—Granger causality test - Abar, Hayri (Economics and Business Review, 2022)
This study aims to investigate the relationship between financial development and economic growth in different time horizons for Turkey. In this study an ensemble of wavelet analysis and Granger causality test were used. PSC was used to represent financial development and GDP was used to represent growth. The annual data used are for the period 1961–2018. The result obtained for a one year period shows that the demand-following hypothesis is valid for Turkey. Financial development is the Granger cause of growth and positively affects growth. The financial sector should be supported for growth in the short term. While there is no causal relationship for the 2–4 year period, bidirectional causality relationships were determined for the periods of 4–8 years, 8–16 years and 16–32 years. Because variables are a Granger cause of each other and affect each other in a positive direction supporting the financial sector is a preferable policy when the purpose is to achieve growth in the long run.